2021
DOI: 10.1002/int.22541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating biological inspiration for biologically inspired design: An integrated DEMATEL‐MAIRCA based on fuzzy rough numbers

Abstract: Biological inspiration evaluation has been widely acknowledged as one of the most important phases in biologically inspired design (BID) as it substantially determines the direction of the following-up design activities. However, it is inherently an interdisciplinary assessment, which includes both the engineering domain and the biological systems. Due to the lack of knowledge at the early stage of product design, the risk assessments mainly depend on experts' subjective judgments, which values are vague, impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In this case, few scholars combined MAIRCA with fuzzy set theory to resolve decision-making issues. For instances, Chatterjee et al [ 30 ] Evaluated the performance of suppliers with a rough MAIRCA technique for green supply chain implementation in electronics industry; Adar and Kilic Delice [ 31 ] modified the MAIRCA model with hesitant fuzzy linguistic term sets; Boral et al [ 32 ] integrated AHP with MAIRCA in a fuzzy environment for fuzzy failure modes and effects analysis; Bagheri et al [ 33 ] identified the uncertainty factors on the constructional project with an extended MAIRCA under hesitant fuzzy circumstances; García Mestanza and Bakhat [ 34 ] presented a fuzzy MAIRCA for evaluating over-tourism; Zhu et al [ 35 ] established an extended MAIRCA model to assess biological inspiration for biologically inspired design in fuzzy rough environments; Ecer [ 36 ] modified the MAIRCA with intuitionistic fuzzy numbers to choose coronavirus vaccine in the age of COVID-19. However, the MAIRCA has neither been extended in a picture fuzzy environment, nor been utilized to deal with teaching quality evaluation issues.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, few scholars combined MAIRCA with fuzzy set theory to resolve decision-making issues. For instances, Chatterjee et al [ 30 ] Evaluated the performance of suppliers with a rough MAIRCA technique for green supply chain implementation in electronics industry; Adar and Kilic Delice [ 31 ] modified the MAIRCA model with hesitant fuzzy linguistic term sets; Boral et al [ 32 ] integrated AHP with MAIRCA in a fuzzy environment for fuzzy failure modes and effects analysis; Bagheri et al [ 33 ] identified the uncertainty factors on the constructional project with an extended MAIRCA under hesitant fuzzy circumstances; García Mestanza and Bakhat [ 34 ] presented a fuzzy MAIRCA for evaluating over-tourism; Zhu et al [ 35 ] established an extended MAIRCA model to assess biological inspiration for biologically inspired design in fuzzy rough environments; Ecer [ 36 ] modified the MAIRCA with intuitionistic fuzzy numbers to choose coronavirus vaccine in the age of COVID-19. However, the MAIRCA has neither been extended in a picture fuzzy environment, nor been utilized to deal with teaching quality evaluation issues.…”
Section: Introductionmentioning
confidence: 99%
“…and Lim C π z (Luo et al 2021). Equations ( 36)-( 39) explain the ways to obtain a total relation matrix (TRM) (Zhu et al 2021). Additionally, the defuzzification process is done by Eqs.…”
Section: Dematel Based On Pfrssmentioning
confidence: 99%
“…The merits of the MAIRCA method are described as below: (1) it can be employed to settle decision-making issues which have multitudinous criteria and alternatives; (2) it can also solve decision problems with mixed quantitative and qualitative evaluation criteria; (3) the decision process of MAIRCA is easily understood and can be flexibly applied in combination with other methods; and (4) the method has a distinctive linear normalization algorithm which can obtain highly reliable discrepancies and produce consistent results. Due to the above merits, many scholars have employed the MAIRCA to settle real-world decision issues in a great number of fields, such as flood susceptibility assessment (Hadian et al, 2022), ammunition depot site selection problems (Gigovic et al, 2016), biological inspiration evaluation (Zhu et al, 2021), supplier performance evaluation (Chatterjee et al, 2018), failure risk evaluation (Boral et al, 2020), business partner selection (Trung et al, 2022), and energy storage technology selection . To indicate the ambiguous and indetermined evaluation information, some scholars have extended the traditional MAIRCA method by combining it into various decision environments, such as classical fuzzy sets (Gul and Ak, 2020;Boral et al, 2020;Mestanza and Bakhat, 2021), fuzzy rough sets (Zhu et al, 2021), spherical fuzzy sets (Trung et al, 2022;Erdogan, 2022), rough sets (Chatterjee et al, 2018;Pamucar et al, 2017a;Bozanic et al, 2020;Pamucar et al, 2017b) and intuitionistic fuzzy sets (Ecer, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above merits, many scholars have employed the MAIRCA to settle real-world decision issues in a great number of fields, such as flood susceptibility assessment (Hadian et al, 2022), ammunition depot site selection problems (Gigovic et al, 2016), biological inspiration evaluation (Zhu et al, 2021), supplier performance evaluation (Chatterjee et al, 2018), failure risk evaluation (Boral et al, 2020), business partner selection (Trung et al, 2022), and energy storage technology selection . To indicate the ambiguous and indetermined evaluation information, some scholars have extended the traditional MAIRCA method by combining it into various decision environments, such as classical fuzzy sets (Gul and Ak, 2020;Boral et al, 2020;Mestanza and Bakhat, 2021), fuzzy rough sets (Zhu et al, 2021), spherical fuzzy sets (Trung et al, 2022;Erdogan, 2022), rough sets (Chatterjee et al, 2018;Pamucar et al, 2017a;Bozanic et al, 2020;Pamucar et al, 2017b) and intuitionistic fuzzy sets (Ecer, 2022). For example, the MAIRCA method was combined with the AHP (Analytic Hierarchy Process) (Boral et al, 2020;Mestanza and Bakhat, 2021) and BWM (Best-Worst Methods) (Gul and Ak, 2020) approaches for obtaining criteria weights to solve the MCDM problem in classical fuzzy sets, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation